HIV-Related Knowledge, Attitudes, Behaviors and Experiences of Kenyan Adolescents Living with HIV Revealed in WhatsApp Group Chats. (3rd March 2021) - Chory, Ashley; Nyandiko, Winstone; Martin, Roxanne; Aluoch, Josephine; Scanlon, Michael; Ashimosi, Celestine; Njoroge, Tabitha; McAteer, Carole; Apondi, Edith; Vreeman, Rachel
Introduction: Mobile technologies represent a scalable platform for delivering knowledge and interventions targeting adolescents living with HIV (ALWH) in low and middle income countries. Data from mobile interventions can be used to assess the contextual understanding and experiences of ALWH. Methods: We examined HIV-related knowledge, attitudes, beliefs, behaviors, and experiences of Kenyan ALWH revealed in the contextual data from enrollment in a WhatsApp® group chat intervention. Results: Thirty ALWH (17 female, mean age 15.4) on ART, engaged in HIV care and aware of their status, were enrolled. Qualitative analysis of WhatsApp® chat discussions identified a gap in HIV knowledge, high medication-taking literacy, need for mental health support and significant barriers to adherence. Participants discussed challenges with HIV stigma and medication-taking in the school setting. Conclusion: These discussions demonstrate a need for education on HIV topics, mental health support for ALWH, and interventions for stigma mitigation in the school setting.